First-principles study of metallic impurities induced 355 nm UV laser absorption in fused silica - Qingyi Feng; Xiaotao Zu; Biyi Wang; Lijie Sun; Bo li; Xia Xiang; Li Li; Ye Tian; Xiaodong Yuan; Wanguo Zheng; Hongdong Yang; Huiqiu Deng; et al. (Journal of Materials Research and Technology, 2022)
To date, it is controversial which metallic impurities play crucial role in the laser induced degradation and damage of fused silica at 355 nm. In this work, a First -principles study for the influences of impurities in fused silica are presented, which are usually contaminated during manufacture and post-processing processes. Our results show that Ca, K, Fe and Ce can lead to obvious optical absorption near 355 nm. Moreover, we find that, for K and Ca, the absorption intensity near 355 nm is highly sensitive to the concentration. Our results indicate that K and Ca can easily induce degradation and damage of fused silica at 355 nm. These two impurities should be concerned during manufacture and post-processing processes. The detailed theoretical study reveal that Ca and K can induce obvious impurity states in band gap and the optical absorption near 355 nm is originated from the transition between impurity states to conduction band. Our results also reveal that, for fused silica with Ca impurity, the exciton effect plays an important role for the optical absorptions near 355 nm, while it is not significant for K. Our work helps to explore laser damage mechanism and improve manufacture and post-processing techniques of fused silica.